(untitled) (Journal of Universal Science Research, 2025)
The article describes the context of evolving linguistic norms influenced by sociocultural shifts, such as the increasing push for gender inclusivity and non-binary representation in language. Analyzing gender units semantically can help identify implicit biases, asymmetries, and stereotypes embedded in the language, contributing to efforts aimed at reducing gender discrimination in communication.